Parental Time Investments in Children: The Role of Competition for University Places in the UK - Almudena Sevilla; Cristina Borra (Institute for the Study of Labor (IZA), 2015)
We use novel diary surveys coupled with universities' administrative student data for the last three decades to document that increased competition for university places at elite institutions in the United Kingdom contributes to explain growing gaps in time investments between college and non-college educated parents. Competition for university places in the UK grew significantly during the 1980s and early 1990s, and gradually diminished afterwards. We find that the gap in time investments by college and non-college educated parents and their children widened up precisely during this first period, especially in terms of human capital enhancing activities.
Keywords: J13; J24; 330; parental time investments; children; college competition